2011
DOI: 10.1007/s10725-011-9631-9
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of phosphorus deficiency stress by moderate salinity in the halophyte Hordeum maritimum L.

Abstract: Hordeum maritimum (Poacea) is a facultative halophyte potentially useful for forage production in saline zones. Here, we assessed whether moderate NaCl-salinity can modify the plant response to phosphorus (P) shortage. Plants were cultivated for 55 days under low or sufficient P supply (5 or 60 lmol plant -1 week -1 KH 2 PO 4 , respectively), with or without 100 mM NaCl. When individually applied, salinity and P deficiency significantly restricted whole-plant growth, with a more marked effect of the latter str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…For example, averaged across all graft combinations, shoot biomass was reduced 30% by low P and 56% by salt stress, yet the combination of these stresses only decreased shoot biomass by 79% (Figure ). Similar non‐additive effects on whole plant biomass (Zribi et al ) and the relative growth rate of wild and cultivated barley (Zribi et al ) were found under combined salt (100 mmol/L NaCl) stress and P deprivation (5 μM P). Moreover, since individual low P and salt stresses had opposing effects on foliar ABA concentrations, the [ABA] leaf of the plants grown under control conditions and those under combined stress were similar (except in the flc /WT plants), although the combined stress substantially increased the [ABA] root and [ABA] xylem compared with the control plants (Figure ).…”
Section: Discussionsupporting
confidence: 61%
“…For example, averaged across all graft combinations, shoot biomass was reduced 30% by low P and 56% by salt stress, yet the combination of these stresses only decreased shoot biomass by 79% (Figure ). Similar non‐additive effects on whole plant biomass (Zribi et al ) and the relative growth rate of wild and cultivated barley (Zribi et al ) were found under combined salt (100 mmol/L NaCl) stress and P deprivation (5 μM P). Moreover, since individual low P and salt stresses had opposing effects on foliar ABA concentrations, the [ABA] leaf of the plants grown under control conditions and those under combined stress were similar (except in the flc /WT plants), although the combined stress substantially increased the [ABA] root and [ABA] xylem compared with the control plants (Figure ).…”
Section: Discussionsupporting
confidence: 61%
“…The underlying mechanism may be the halophytes taken up the P from rhizosphere and being P is immobile so high P concentration was observed in bulk soil. Previously, P depleted zone was also observed in the rhizosphere (Liangpeng et al, 2008) and salinity mitigate the adverse effects of P deficiency on halophyte (Zribi et al, 2012). Exchangeable K and Na level was greater in the rhizosphere than those in bulk soil.…”
Section: Soil Characteristics and Nutrient Contentmentioning
confidence: 76%
“…Contrary to observation of Shao et al (), available P concentration was also significantly influenced by the halophyte plant species; however, P availability is regulated by soil adsorption rather than biological processes (Marschner, ). The underlying mechanism of high concentration of P under halophyte‐covered soils compared with that in control soil may be due to the higher alkaline phosphatase activity under halophyte‐covered soils, which mineralize the P adsorption, and salinity mitigates the adverse effects of P deficiency on halophyte (Chaudhary et al , ; Zribi et al , ). The Na concentration was low under halophyte‐covered soils than in control soil (Table ) because these halophytes can absorb Na and reduce the concentration in soil (Cao et al , ).…”
Section: Discussionmentioning
confidence: 99%